2018
DOI: 10.1590/s2175-97902018000317447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community pharmacists’ involvement in public health activities in Nigeria

Abstract: The aims of the study were to identify the types, determine the extent of community pharmacists' involvement, and evaluate the factors influencing their participation in public health activities in Nigeria. The study was a cross-sectional survey of randomly selected 130 registered community pharmacies. Pretested questionnaire was the instrument for data collection. Descriptive and inferential statistics were used to analyse data. Response rate was 94.9%. The study identified 31 types of public health activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 31 publications
(37 reference statements)
3
19
0
Order By: Relevance
“…The study sample had slightly more male respondents than females, and most respondents (above 80%) were young adults below the age of 40 years. The highest qualification for the majority (above 70%) of the respondents was the first degree, while the work-related experience was less than 10 years for most (about 80%) respondents, this is supported by a study done by Kanayo Patrick Osemene and Wilson O Erhun [12] in which there were more male than females within the age 18-34 years in community pharmacies. More than half of the respondents were married, and the majority reported Christianity as their religion.…”
Section: Discussionmentioning
confidence: 71%
“…The study sample had slightly more male respondents than females, and most respondents (above 80%) were young adults below the age of 40 years. The highest qualification for the majority (above 70%) of the respondents was the first degree, while the work-related experience was less than 10 years for most (about 80%) respondents, this is supported by a study done by Kanayo Patrick Osemene and Wilson O Erhun [12] in which there were more male than females within the age 18-34 years in community pharmacies. More than half of the respondents were married, and the majority reported Christianity as their religion.…”
Section: Discussionmentioning
confidence: 71%
“…The data re-enforce earlier evidence. 3,20,31,32 In summary, it may be concluded that community pharmacists are PHC service providers, actively involved in all eight domains of PHC.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the ease of access, short waiting time, free consultation, and longer-term availability of the community pharmacists to the people [ 6 ]. For this position, pharmacists have been reinventing themselves to meet the dynamic health demands of the community [ 7 ]. One of such demands is the provision of mental health services for patients with such needs.…”
Section: Commentarymentioning
confidence: 99%
“…These services range from counseling on traumatic life experiences to facilitating therapy for addiction and depressive disorders among others. In fact, Osemene and Erhun [ 7 ] underscored counseling as the most common self-reported participation in non-pharmacologic public health activities among community pharmacists. Also, given its strategic position, community pharmacy-based provision of behavioral activation therapy for the treatment of depression is considered viable and efficient [ 5 ].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation